Desain Data Flow Diagram dan Flowchart Pada Siklus Pengeluaran Kas Percetakan Maleo Printing di Kota Ambon - Reawaruw, Virgin Airin; Tuaputty, Jaleha; Bahtiar, Sari Rahmadani; Aprilia, Faradila Putri; Julianti, Andini; Tuhumury, Ana Masye; Theris, Angelica Eklesia; Rehatta, Gabriel; Mustamu, Merlyn; Baker, Misyel (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas KH. A. Wahab Hasbullah, 2025)
This community engagement project aims to assist small businesses in designing an accounting information system that supports efficiency in the cash expenditure cycle. The activity was carried out at a small printing business, Maleo Printing, located in Ambon City, which still manages its cash disbursement transactions informally. The purpose of this project is to analyze the existing procedures and develop system documentation in the form of Data Flow Diagrams and Flowcharts to visualize the flow of information and operational procedures. Through a service learning approach, students conducted field observations, interviews, data analysis, and system modeling based on the business’s needs. The outcomes include a context diagram, level 0 and level 1 DFDs, as well as structured flowcharts that depict the processes of ordering, payment, and recording of cash outflows systematically. These designs help business owners understand their workflows, improve documentation, and serve as a preliminary reference for developing a simple computer-based information system. This experience also enriched students’ understanding of the real-world application of accounting information system theory. Overall, the project demonstrates that the development of DFDs and Flowcharts offers a practical solution for small businesses in building a more structured and efficient recording system.